ANALISIS FUNGSI DAN MAKNA MANTRA PENGOBATAN SUKU DAYAK MERATUS DESA BATULASUNG KECAMATAN KELUMPANG HULU KABUPATEN KOTABARU - Husni Mubarak (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2019)
The purpose of this study was (1) To describe the Medical Mantra Function of Meratus Dayak Community Batulasung Village, Kelumpang Hulu District, Kotabaru Regency. (2) To describe the Meaning of Medical Treatment of the Meratus Dayak Community of Batulasung Village, Kelumpang Hulu District, Kotabaru Regency. The method used in this research is descriptive qualitative research, the data collected are in the form of words, images and not numbers. The data analysis technique used descriptive interpretative, the researcher explained through the stages: (a) transcription of recorded data, i.e. transferring data in the form of oral data written by spell dayak transferred to oral form (b) data classification, i.e. all data in the form of dayak spell text is collected in accordance with the characteristics and classification of content (c) data translation, i.e. at this stage all data that has been grouped and still in the original form is translated into Indonesian (d) data analysis, at this stage the researcher analyzes all the data collected by function, and the meaning of the mantra. The results of the discussion from this study are the mantra of treatment (used for oneself or only in the family) and are social (used for his own benefit, but can also be used to help others in healing and alleviating the pain suffered by the community) so that it is beneficial for the public a lot. Keywords: The function of the treatment mantra and the meaning of the treatment mantra